The Role of YLBHI-LBH Semarang in Providing Legal Aid to Victims of the Omnibus Law Demonstration: A Discourse of Freedom of Expression and Press in Indonesia - Ramadani, Muhammad Fahmi; Holish, Amarru Muftie (Indonesia Media Law Review, 2023)
Legal aid is the provision of legal aid services to those who can afford achievements or to give voluntarily to the poor. The provision of Legal Aid is an advocate profession. The provision of legal assistance provides a sense of peace of mind to the recipients of legal assistance. The purpose of this paper is to determine the function and authority of the Indonesian Legal Aid Foundation as a provider of Legal Aid and the problems faced by the Indonesian Legal Aid Foundation in accompanying victims of omnibus law demonstrations. This study aims to analyze the role of YLBHI-LBH Semarang in providing protection for victims. In addition, this study also analyzes the rights of citizens in expressing and expressing opinions in the context of freedom of opinion and the press in Indonesia. This study found that in terms of victim protection, especially demonstrations by legal aid agencies, there were many obstacles, especially repression from law enforcement officials. In addition, journalists and the press, including the legal aid press, are also often under pressure, ranging from threats, persecution, to damaging the press media on the ground. In fact, freedom of the press and victim protection are guaranteed in Indonesian law.